The Doctrine of Creation: A Constructive Kuyperian Approach - Ashford, Bruce Riley (InterVarsity Press, 2020)
According to Bruce Ashford and Craig Bartholomew, one of the best sources for regaining a robust, biblical doctrine of creation is the recovery of Dutch neo-Calvinism. Tracing historical treatments and exploring theological themes, Ashford and Bartholomew develop the Kuyperian tradition's rich resources on creation for systematic theology and the life of the church today.